2006
DOI: 10.1111/j.1399-0004.2006.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis imperfecta: clinical, biochemical and molecular findings

Abstract: Mutations in COL1A1 and COL1A2 genes, encoding the alpha1 and alpha2 chain of type I collagen, respectively, are responsible for the vast majority of cases of osteogenesis imperfecta (OI) (95% of patients with a definite clinical diagnosis). We have investigated 22 OI patients, representing a heterogeneous phenotypic range, at the biochemical and molecular level. A causal mutation in either type I collagen gene was identified in 20 of them: no recurrent mutation was found in unrelated subjects; 15 out of 20 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
5
30
0
2
Order By: Relevance
“…COL1A1 is 18 kb in size and is located at 17q21.3-q22. COL1A2 is 38 kb and is located at 7q21.3-q22.1 (Vuorio and de Crombrugghe, 1990;Venturi et al, 2006). The two genes are similar in structure: COL1A1 and COL1A2 have 51 and 52 exons, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…COL1A1 is 18 kb in size and is located at 17q21.3-q22. COL1A2 is 38 kb and is located at 7q21.3-q22.1 (Vuorio and de Crombrugghe, 1990;Venturi et al, 2006). The two genes are similar in structure: COL1A1 and COL1A2 have 51 and 52 exons, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigators have reported on the dental status of OI patients with glycine mutations in this region of the collagen type I triple helix and none of the nine patients mentioned in these reports had clear clinical evidence of dentinogenesis imperfecta. [14][15][16][17][18] The mechanistic link between collagen type I mutations and dentinogenesis imperfecta has not been elucidated in any detail. Our data nevertheless show that patients sharing the same mutation had a high concordance for the condition.…”
Section: Resultsmentioning
confidence: 99%
“…type II. Most OI cases are caused by heterozygosity of dominant mutations in one of the two genes encoding the chains of type I collagen (COL1A1 and COL1A2) (3), with quantitative (-qt; mild or moderate forms) or qualitative (-ql; severe or lethal forms) defects of the synthesis of type I collagen (4). Cartilage-associated protein (CRTAP), prolyl 3-hydroxylase 1 (P3H1/LEPRE1), and cyclophilin B (CyPB/PPIB) form an intracellular collagen-modifying complex that 3-hydroxylates proline at position 986 (P986) in the a1 chains of collagen (types I, II, and V); mutations in these essential cofactors cause alterations in the posttranslational chain modification and collagen folding, which are responsible for autosomal-recessive lethal or severe OI (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%